Yacht Design and Maritime Landscape: Continuity in artisan Culture - Eleonora Trivellin (Agathón)
The paper highlights the matrices of Mediterranean navigation and the relationship with artisan work processes, as well as how they have continued to characterize the nautical field and how research has identified themes which today seem to be able to characterise a culturally and economically important sector such as that of the production of sports yachts.